2011
DOI: 10.1021/ja110638y
|View full text |Cite
|
Sign up to set email alerts
|

Oxide Nanotubes on Ti−Ru Alloys: Strongly Enhanced and Stable Photoelectrochemical Activity for Water Splitting

Abstract: The present work shows a significant enhancement of the photoelectrochemical water-splitting performance of anodic TiO(2) nanotube layers grown on low concentration (0.01-0.2 at% Ru) Ti-Ru alloys. Under optimized preparation conditions (0.05 at% Ru, 450 °C annealing) the water splitting rate of the oxide tubes could be 6-fold increased. Moreover, the beneficial effect is very stable with illumination time; this is in contrast to other typical doping approaches of TiO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 31 publications
1
88
0
1
Order By: Relevance
“…Since the first report of solar-driven photoelectrochemical energy conversion in 1972 by Fujishima and Honda, TiO 2 has been widely investigated as the most promising material for photocatalytic applications due to its high photocatalytic activity and photochemical stability [1][2][3][4][5][6][7]. Compared with other TiO 2 films prepared by chemical vapor deposition (CVD) [8,9], liquid-phase deposition (LPD) [10,11], sol-gel synthesis [12] and magnetron sputtering deposition methods [13], the electrochemical anodization method is regarded as one of the relatively simple techniques to synthesize TiO 2 nanotubes with large surface area [14][15][16]. Moreover, the one-dimensional and highly ordered nanotube architecture offers an excellent electrical channel for vectorial charge transfer so that photoinduced electron-holes pairs can be effectively separated, resulting in an obvious improvement in the photoelectochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of solar-driven photoelectrochemical energy conversion in 1972 by Fujishima and Honda, TiO 2 has been widely investigated as the most promising material for photocatalytic applications due to its high photocatalytic activity and photochemical stability [1][2][3][4][5][6][7]. Compared with other TiO 2 films prepared by chemical vapor deposition (CVD) [8,9], liquid-phase deposition (LPD) [10,11], sol-gel synthesis [12] and magnetron sputtering deposition methods [13], the electrochemical anodization method is regarded as one of the relatively simple techniques to synthesize TiO 2 nanotubes with large surface area [14][15][16]. Moreover, the one-dimensional and highly ordered nanotube architecture offers an excellent electrical channel for vectorial charge transfer so that photoinduced electron-holes pairs can be effectively separated, resulting in an obvious improvement in the photoelectochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Absence of RuO2 diffraction patterns in RuXTi1-XO2 is ascribed to the fine dispersion of ultra-small, subatomic RuO2 clusters in TiO2 clusters as well as its inclusion in host TiO2 matrix. 21 Fig .-1: The image of peroxide sols, heterogeneous solution containing nanocrystals after the hydrothermal treatment and the toluene dispersion of the nanocrystals (a) yellow transparent Titanium sol (b) heterogeneous mixture of titania (TiO2) crystals (c) stable dispersion of (TiO2) crystals, (d) brown coloured titania ruthenium sol2 (e) heterogeneous mixture of ruthenium doped titania(RuXTi1-XO2) crystals (f) stable dispersion of RuXTi1-XO2…”
Section: Resultsmentioning
confidence: 99%
“…Yet, relatively low solar utilization percentage of TiO 2 material remains a challenge due to its large band gap (3.2 eV for anatase and 3.0 eV for rutile). Researches have shown that introduction of defects or dopants into the TiO 2 lattice can extend the absorption spectrum of TiO 2 into visible light region [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%